ANALISIS KEBERLANJUTAN PERMUKIMAN NELAYAN GAMPONG ALUE NAGA KOTA BANDA ACEH - Arif Farhanawan; Halis Agussaini*; Zahrul Fuady (Rumoh Journal of Architecture, 2022)
On December 26, 2004, the coastal area of the city of Banda Aceh experienced total destruction, both physically and non physicallyas a result of a 9-magnitude earthquake followed by a tsunami. A year later this area was restored to its condition through the Rehabilitation and Reconstruction Agency formed by the government of the Republic of Indonesia with a four year working period. Alue Naga is one of the urban village where local community is still depend on their livelihood as fishermen. This study aims to analyze the level sustainability of fishermen's settlements in Alue Naga after destroyed by tsunami. The method used in this study is a sustainability analysis technique using RAPFISH (Rapid Appraisal for Fisheries) in a multidimensional manner. Community economic condition analysis is calculated based on four attributes, the same way goes to analysis of social condition and environmental condition. All of this makes 12 sustainability attributes. The results showed that Alue Naga settlement in terms of the pillars of economic sustainability had an index value of 31.82, this number means unsustainable. Likewise, the environmental pillar is still unsustainable with an index value of 35.54. Meanwhile, the social pillar is sustainable with an index value of 59.98. Overall (multidimensional) the settlement status of Alue Naga falls into the unsustainable category with an index value of 42.44. There are six sensitive attributes that have an influence on increasing the sustainability status and they need to be maintained. Six insensitive attributes that have a low effect needs to be improved in order to achieve the sustainability status.